How we tried to JATS XML - Odu, Obiajulu; Ekanger, Aysa (Ravnetrykk, 2020)
This is a story about how an Open Journal Systems-based library publishing service tried (and failed) to implement XML in one of its publications. We ran a small project to look at how journals we support could develop a JATS XML-based publishing workflow using existing open software tools.